Assessment of Validity and Reliability of Attitude towards Science Scale - Chandni Sharma (Research Aspects in Arts and Social Studies Vol. 2, 2022)
The current study is concerned with the establishment of an Attitude towards Science Scale based on the TOSRA (Test of Science-Related Attitudes) and anxiety towards science. The study included students between the ages of 14 and 15 from government schools in Chandigarh, India. Exploratory factor analysis was used to demonstrate the scale’s validity, and confirmatory factor analysis was used to confirm the final factor structure. Following the validation of the scale’s content, 42 items were subjected to principal axis factoring, which showed 5 factors with a total variance explained of 78%. Anxiety about science, appreciation of science classes, adoption of scientific attitudes, enjoyment of science lessons, and societal implications of science were identified as these dimensions. In order to further confirm the theoretical model of five factors confirmatory factor analysis was used for which the model fit indices were found to be(CMIN = 3.00, RMR= 0.045, CFI= 0.895, TLI= 0.884, RMSEA=0.100) and the model was considered to be reasonably well fit with a reliability of 0.92 determined using Cronbach Alpha.